2016
DOI: 10.3390/brainsci6040061
|View full text |Cite
|
Sign up to set email alerts
|

Body-Machine Interfaces after Spinal Cord Injury: Rehabilitation and Brain Plasticity

Abstract: The purpose of this study was to identify rehabilitative effects and changes in white matter microstructure in people with high-level spinal cord injury following bilateral upper-extremity motor skill training. Five subjects with high-level (C5–C6) spinal cord injury (SCI) performed five visuo-spatial motor training tasks over 12 sessions (2–3 sessions per week). Subjects controlled a two-dimensional cursor with bilateral simultaneous movements of the shoulders using a non-invasive inertial measurement unit-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Since sensory input is often altered after SCI 7 , an advantage of making sensory predictions is that the brain does not have to wait for sensory input to act. For example, studies using body-machine interfaces found that humans with SCI improve their limb function by learning a predictive map between their residual motion and a low dimensional control space 68 , 69 . If cerebellar atrophy limits the ability to adapt movements to new demands, some strategies might be helpful to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Since sensory input is often altered after SCI 7 , an advantage of making sensory predictions is that the brain does not have to wait for sensory input to act. For example, studies using body-machine interfaces found that humans with SCI improve their limb function by learning a predictive map between their residual motion and a low dimensional control space 68 , 69 . If cerebellar atrophy limits the ability to adapt movements to new demands, some strategies might be helpful to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that training upper body movements with a BoMI increased muscle strength and range of motion in individuals with complete injuries [9], improved symmetry and altered the pattern of muscle activity [11]. In addition, some preliminary studies suggested that the interface can be reprogrammed to progressively encourage participation in skilled activities of more distal parts of the body [10,52].…”
Section: Co-adaptation For Therapymentioning
confidence: 99%
“…Recently, BoMI's have been proposed as instruments for functional retraining [10][11][12]. In the rehabilitative context, the BoMI can be configured to represent specific patterns of coordination that would be desirable for the user to practice/learn, that take the form of a forward map from body motion to effector positions.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the operation of an assistive machine that replaces lost function also might be used to regain lost function. We are starting to see this explored with novel interfaces that provide rehabilitation benefits through their operation (149), and are used to control computers and wheelchairs. A therapy paradigm might adapt how much and what sort of autonomy assistance is provided by the robot, in order to encourage the recovery of motor function-as we have seen in machines whose purpose it is to rehabilitate the body (145,146).…”
Section: Gold Standard: Assistive Robots That Rehabilitatementioning
confidence: 99%